Blockchain Adoption Factors - Bernardino, Carlos (2025)
Bernardino, C., Cesário, F., Costa, C. J., Aparício, M., & Aparício, J. T. (2025). Blockchain Adoption Factors. International Journal of Information Systems and Project Management, 13(1), 1-23. Article e3. https://doi.org/10.12821/ijispm130103